Budaya Kerja dan Organizational Citizenship Behavior (OCB) pada Karyawan Frontliner Generasi Z: Peran Mediasi Motivasi Intrinsik - Mutiara Ainul Hikmah; Abdul Aziz Nugraha Pratama (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
This study investigates the influence of organizational culture on Organizational Citizenship Behavior (OCB) among Generation Z frontline employees at PT. PIP, with intrinsic motivation serving as a mediating variable. Utilizing a quantitative survey approach and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis, the findings reveal that supportive organizational culture exerts both direct and indirect positive effects on OCB through intrinsic motivation. Key results demonstrate that a supportive culture strengthens employees' internal motivation, which in turn fosters extra-role behaviors. This research integrates Denison's Organizational Culture Model, Self-Determination Theory (SDT), and Organ's OCB framework, addressing theoretical gaps in Generation Z hospitality contexts. Practical implications offer actionable HR strategies for the tourism industry, particularly in reducing employee turnover and enhancing organizational effectiveness by cultivating adaptive cultures that fulfill psychological needs among digital-native frontline workers.